Personality-guided forensic psychology - Craig, Robert J. (Personality-guided psychology / series editor Theodore Millon, 2005)
(from the preface) This book attempts to bridge these bodies of scientific literature and practice by demonstrating the central role of personality and personality disorders in the assessment of patients within the context of court-related issues and problems. It illustrates how personality-guided assessment adds to what the psychometricians might call "incremental validity," what the social psychologists might call "ecological validity," and what triers of fact (judges and juries) might call "the truth." The material in this book concentrates on the assessment of adults. However, in a few sections, material related to the assessment of juvenile offenders is included, especially the assessment of psychopathy and violence risk assessments